Application cases of biological transformation in manufacturing technology. (November 2020) - Bergs, T.; Schwaneberg, U.; Barth, S.; Hermann, L.; Grunwald, T.; Mayer, S.; Biermann, F.; Sözer, N.
Abstract: Digitalization and Industry 4.0 are promising developments for solving current technical challenges. However, to fully exploit the potential of digitalization and Industry 4.0, not only manufacturing and information systems must interact, but biological systems too. The interaction of biological, manufacturing and information systems is an emerging research field defined as Biological Transformation in manufacturing or biologicalisation in manufacturing. This publication introduces three different projects that represent the application of Biological Transformation in manufacturing to inspire and initiate further research in this area. The interactions of the three system types are described in detail, and their potential for the manufacturing sector is discussed in reference to the framework Biological Transformation in manufacturing.